Uremic Cardiomyopathy: An Underdiagnosed Disease. Issue 4 (25th April 2013) - Alhaj, Eyad; Alhaj, Nehad; Rahman, Ifad; Niazi, Tariq O.; Berkowitz, Robert; Klapholz, Marc
Abstract : Uremic cardiomyopathy is responsible for high morbidity and mortality rates among patients with chronic kidney disease (CKD) or end‐stage renal disease (ESRD); however, the early implementation of hemodialysis may halt its progression. Nonconventional hemodialysis, such as frequent hemodialysis, appears to have an advantage over conventional hemodialysis. Kidney transplantation has been shown to reverse uremic cardiomyopathy and to confer a significant survival advantage over hemodialysis. Targeting future therapies at the underlying cellular mechanisms of uremic cardiomyopathy may finally start to reduce the burden of uremic cardiomyopathy in the CKD and ESRD population.